THE NEW RESPONDS TOWARD THE CHALLENGE: ISLAMIC DA'WAH AND CATHOLIC MISSION IN SEMARANG, 1890s-1940s (History Department, Semarang State University and Historian Society of Indonesia, 2015)
This study discusses the growth and development of religious movements and their effects on social life of religious communities during the period 1890s-1940s Semarang. The main problems of this study are the growth and development of Islamic da’wah and Catholic mission and its influence on socio-religious life to the people in Semarang. This study used the historical method in order to answer the problem. The development of Islamic da'wah and Catholic missions in Semarang in the period 1890s-1940s could be seen into two mainstream, namely the renewal of da’wah and indigenization of mission. Islamic da'wah and Catholic mission have brought progress to the social religious life of societies. Poeple in Semarang recognized the religious organization and new forms of leadership which more rational and democratic, and the growth of new awareness of identity from people to the identity as citizens. Penelitian ini mendiskusikan muncul dan berkembangnya gerakan keagamaan dan dampaknya pada kehidupan sosial pada komunitas agama periode 1890-an sampai 1940-an di Kota Semarang. Permasalahan utama dalam penelitian ini adalah pertumbuhan dan perkembangan dakwah Islam dan misi Katolik, serta pengaruhnya terhadap kehidupan sosial keagamaan di Semarang. Penelitian ini menggunakan metode sejarah untuk menjawab permasalahan. Perkembangan dakwah Islam dan misi Katolik pada periode 1890-an sampai 1940-an dapat dilihat dari dua mainstream, yakni pembaharuan dakwah dan indigenisasi (pelokalan) dari misi. Dakwah Islam dan misi Katolik memberikan progress terhadap kehidupan sosial keagamaan di Semarang. Masyarakat di Semarang mengenal organisasi keagamaan dan bentuk baru dari kepemimpinan yang lebih rasional dan demokratis, dan tumbuhnya kesadaran atas identitas personal menjadi identitas sebagai warga masyarakat.